A Bibliometric Perspective of Green Computing - Loso Judijanto (Westscience Press, 2026)
Green computing has emerged as a vital field in response to growing concerns over the environmental impact of computing technologies. This study presents a bibliometric analysis of the green computing research landscape, examining key research themes, influential contributors, and emerging technologies. By analyzing a comprehensive dataset of academic publications, this study reveals the growing emphasis on energy-efficient computing systems, particularly in areas such as cloud computing, mobile edge computing, and machine learning. The analysis highlights the increasing role of interdisciplinary collaborations and global contributions to green computing research. Additionally, the study identifies key emerging trends, such as the integration of energy-efficient solutions with advanced technologies like 5G, IoT, and blockchain. This paper provides valuable insights into the current state of green computing research and offers a roadmap for future advancements in sustainable computing technologies.